Quantity of spontaneous touches to body and surface in very preterm and healthy term infants - Stupperich, Sophie; Dathe, Anne-Kathrin; DiMercurio, Abigail; Connell, John P.; Baumann, Nicole; Jover, Marianne; Corbetta, Daniela; Jaekel, Julia; Felderhoff-Mueser, Ursula; Huening, Britta (Frontiers in Psychology, 2024)
BackgroundSpontaneous movements are a crucial part of early motor development. Healthy term infants may produce up to 200 spontaneous touches to their body and surface in 10 minutes with their hands. The existing literature shows differences in early motor development between very preterm (<32 weeks gestation) and healthy term infants. It is not known whether the quantity of spontaneous touches differs between very preterm infants and healthy term infants.AimsThis study investigates whether the overall quantity of spontaneous touches to body and surface is lower among low-risk very preterm infants compared with healthy term infants.MethodsVideos of 25 low-risk very preterm infants (10 female) at a mean corrected age of 13 weeks [Mean = 12.76, Standard Deviation (SD) = 1.07] were recorded during clinical routine and compared with videos of five healthy term infants (chronological mean age = 9.00, SD = 0.63). Spontaneous touches of both hands were coded, assessing number and location of each touch (i.e., body vs. surface).ResultsVery preterm infants showed significantly fewer overall touches per minute (Mean = 8.87, SD = 4.13) than healthy term infants (Mean = 13.19, SD = 4.28), 95% Confidence Interval (CI) = [0.00, 6.84] (p = 0.029).Discussion and conclusionThis study shows that low-risk very preterm infants, on average, produce fewer spontaneous touches than healthy term infants at three months of corrected age. The present study provides important exploratory evidence for further studies, particularly longitudinal investigations of all dimensions of development.